Cardiovascular Disease and Mental Health in Intellectual Disabilities: A Vicious Cycle of Risk and Care Gaps - Yadav, Abhishek Pratap; Lata, Suman; Awasthi, Anita; Katiyar, Praveen; Shukla, Priyanka; Vishwakarma, Avaneesh; Singh, Sandeep Kumar (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Background: Cardiovascular diseases (CVDs) are the primary reason for demise and disability worldwide, with a particularly severe problem in low- and middle-income nations. Among individuals with intellectual disabilities (ID), the coexistence of cognitive impairments, mental health conditions, and barriers to medical care significantly increases health risks. Objective: This review discovers the bidirectional connection between cardiovascular disease and mental health disorders in individuals with ID. It aims to classify risk factors, examine care disparities, and evaluate the need for targeted interventions. Methods: A descriptive review methodology was employed. A total of 1,182 articles were initially retrieved from PubMed, Scopus, and PsycINFO using a focused keyword strategy encompassing CVD, mental health, and intellectual disability. After applying inclusion criteria centered on disability relevance and peer-reviewed content, 914 articles were shortlisted. From these, 173 studies were selected based on quality and contextual suitability. Results: The review identified a consistent pattern of underrepresentation of individuals with ID in cardiovascular and psychiatric research despite their increased rates of congenital heart defects, lifestyle-related risk factors, and untreated mental health issues. Diagnostic overshadowing, resource constraints for caregivers, and a lack of appropriately adapted therapies further aggravate their vulnerability. Evidence suggests that caregiver-supported and community-based interventions, when customized for this population, can improve health outcomes. Conclusion: The interplay between cardiovascular disease and mental health in people with ID constitutes a complex clinical and public health challenge. A disability-sensitive research and care framework is urgently needed. Future approaches should focus on early screening, tailored interventions, integrated care models, and inclusive health policies to adequately support this marginalized population.